Tourism Village Development Strategies in East Bolaang Mongondow Regency - Sulistio, Tigo; Mokat, Jetty E. H.; Kairupan, Sisca B.; Mandagi, Marthinus (Technium Social Sciences Journal, 2025)
This research aims to formulate a strategy for developing tourism villages in East Bolaang Mongondow Regency as an effort to improve the local economy, preserve culture and maintain environmental sustainability. Eastern Bolaang Mongondow Regency has rich natural and cultural potential, but has not been optimally managed to be developed as a sustainable village tourism destination. Using a qualitative method, this research focuses on the development strategy of tourism villages through indicators of funding sources, improving the quality of human resources, maintaining facilities and infrastructure, and improving infrastructure. The results showed that the development of Atoga River View tourism village in East Atoga Village, East Bolaang Mongondow Regency, requires strengthening strategies in four main aspects: financial resources, human resources, facilities and infrastructure, and infrastructure improvement. 1) The availability of adequate funding is key to the sustainability of tourism village development. Funding comes from the Village Fund, central, provincial and local government assistance, and other external parties. Transparent financial management ensures that funds are used for the benefit of the community, facility maintenance, and further development. 2) Local community participation in tourism village management is essential. Training and skills upgrading help the community contribute actively, so that the economic benefits are directly felt by them. 3) Adequate facilities enhance tourist comfort, while infrastructure supports the smooth operation and attractiveness of the destination. 4) Good infrastructure, such as roads and transportation, facilitate tourist access, increase comfort, and encourage local economic growth. The synergy between these four aspects is key to the successful development of Atoga River View tourism village to improve competitiveness and sustainability.